ANÁLISE DE RISCO DE COLISÕES DE AVES EM GERADORES EÓLICOS: UMA NOVA METODOLOGIA - Sales Júnior, Luis Gonzaga; Rezende, Carla Ferreira; Coutinho, Alysson Guedes; Azevedo, Raul (Revista Nordestina de Zoologia, 2023)
The growing socioeconomic development on the planet has been demanding more and more electricity, worrying public policies and energy planning in emerging countries – Here there needs to be some connection that gives meaning to the phrase, it seems confusing –, such as Brazil. In this way, the use of clean energy sources can be an alternative in the medium and long term, such as solar, wind and tidal energy. Studies regarding environmental impacts on bird fauna in wind farms in Brazil are still scarce and are mainly based on measuring bird mortality rates, underestimating the data related to the finding of carcasses of small birds such as Passeriformes and small migratory birds, especially Charadriiformes (Charadriidae and Scolopacidae). As a result of this lack of adequate methods to map and diagnose the real impact of wind turbines on avifauna, the present work aims to launch a methodological proposal to serve as a basis for analysis of the risk of collision between birds and wind turbines in wind farms. The methodology proposed here was developed to be applied in any ornithological study, involving wind turbines, regardless of their size and location, applying both engineering (wind turbine turbine), environmental (plant typology, ecosystems) and ornithological (behavior, size, weight, foraging). – And what results were found? What can be concluded from the case study and the proposed new methodology? The abstract must contain all parts of the work, so that the reader understands what the work aimed at, how it was done and what results were obtained. Although the focus of this article is to present the present methodology, it can be inferred that after inserting the data in the spreadsheet and analyzing the sum of the points of each existing category, the species Coragyps atratus presented High Risk, while the species Cathartes burrovianus, Ardea alba, Caracara plancus and Cathartes aura showed moderate risk of collision with wind turbine blades.